Leadership and Conflict Management: Strategies for Managing Conflict in Higher Education Institutions - Haya, Haya (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study analyzes conflict management strategies through adaptive leadership models to improve educational institutional performance. This study uses a qualitative case study approach. Data collection was carried out through interviews, observations, and documentation. Data analysis used a thematic analysis approach, coding and identifying main themes related to leadership strategies and conflict management. The study results indicate that transparent and open leadership, developing clear conflict policies, creating a collaborative culture, and utilizing a proactive approach are the main strategies that can reduce the frequency and impact of conflict. These findings emphasize the importance of adapting leadership strategies based on local contexts and organizational culture to improve the effectiveness of conflict management. The implications of this study include providing new insights for leaders of higher education institutions to develop more relevant and contextual conflict management policies and practices. This study also suggests the need for further research to expand the scope of research by considering variations in gender, age, and wider survey methods to obtain a more comprehensive picture. Thus, the results of this study can contribute to developing more effective conflict management policies in higher education environments.